Bagaimanakah Lemahnya Tata Kelola Perusahaan Dapat Mendorong Akuntansi yang Kreatif dalam Menciptakan Ilusi Laporan Keuangan? - Maccauley Riyono, Kenley; Stanley, Nicklaus; Easter, Rafael Savio; Adijaya, Vincent; Purnomo, Ruben Putranto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effectiveness of capital market regulations and financial reporting standards in Indonesia in mitigating fraudulent financial performance manipulation. The research sample focuses on PT Garuda Indonesia (Persero) Tbk. during the periods 2017–2018 and 2022–2023. The research was conducted using the content analysis method and literature review to explore the financial statements and sustainability reports in depth. The study examines aspects such as ownership structure, board structure, executive incentives, CEO duality, audit quality, and financial pressure to assess corporate governance, while indications of manipulation are identified using the Beneish M-Score. The results show that the effectiveness of financial statements as a tool for economic decision-making still faces significant challenges due to biases arising from agent behavior. Thus, the effectiveness of capital market regulations and financial reporting in Indonesia has not yet fully succeeded in reducing the risk of financial statement manipulation.